The manifestation and potential of constructive journalism in South African digital news - Fölscher-Kingwill, Barbara (Centre for Film and Media Studies, 2023)
This study aimed to establish the manifestation of constructive journalism, and the perceptions and attitudes of journalists and editors towards the form, in South African digital news. A qualitative content analysis was applied to a sample of 134 articles on “evictions” (written during SA's first Covid lockdown in 2020) from three online news-outlets varying in editorial approach. Semi-structured interviews with a purposively selected sample of journalists and editors followed. Findings showed that the most distinctive principles of constructive journalism were largely absent in the articles. Yet, interviewees recognised a role for the form to be introduced alongside watchdog journalism. Views ranged from supporting constructive journalism as a necessary and valuable approach that would strengthen watchdog journalism, to seeing constructive journalism as a “nice to have” in the overall news cycle. In some of the outlets, constructive journalism has recently been included in output, even if not labelled as such. The contrast between the two dataset's findings indicates a shift in how some journalists have started thinking about the information needs of audiences and ways to address those. Journalists showed acute awareness of the effects of relentless negative news on audiences. Findings revealed that industry pressures posed significant challenges to the implementation of constructive journalism, but that certain of those challenges are also opportunities. One proposition was that newsrooms collaborate to tackle big-issue projects through creating joint investigative/constructive teams. Some journalists had difficulty with a clear conception of constructive journalism but found it noteworthy to see constructive journalism as an additional step in the overall news cycle not replacing their monitorial role. Interviewees wanted to learn more about expanded interviewing techniques proposed in constructive journalism to add complexity to conflict reporting. The study enriches understanding of the applicability of constructive journalism in developing democracies and shows that the form can add nuance and complexity to current practices of watchdog journalism dominating South African news-reporting. The risks of constructive journalism being misinterpreted or manipulated by partisan media requires of journalists to adhere to rigorous journalistic norms proposed in constructive journalism.